EFFICACY OF SUPPLEMENTATION OF PROBIOTICS ALONG WITH ANTIMICROBIAL AGENTS IN VULVOVAGINAL INFECTIONS IN A TERTIARY CARE HOSPITAL - PATIL, DEEPA; S, GEETHA; SHIVAMURTHY, RAGHUPRASADA MALLADAR; N PATIL, UMAKANT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study were to ascertain the efficacy of probiotics along with antimicrobials in the treatment of vulvovaginitis and to evaluate the rate of recurrence. Methods: The study was done on 60 patients who were randomly selected and divided into two groups of 30 each. Prior permission from the Institutional Ethics Committee and higher authorities was obtained before conducting the study. One group received standard treatment including antibacterial, antiviral, and antifungal as per the gynecologist discretion and in other group along with standard treatment, probiotic capsules containing combination of Saccharomyces boulardii, Lactobacillus sporogenes (50 million), Streptococcus faecalis (30 million), Clostridium butyricum (2 million), and Bacillus mesentericus (1 million) given orally twice daily and followed up for a period of 3 months. The drugs were started on the 5th day after menstruation taking starting of the bleeding as day 1. Results: The parameters compared were symptoms and signs (significantly reduced – p-value), clue cells (significantly reduced in number), and recurrence rates (significantly reduced), in 80% of patients smears which were not consistent with BV. Maximum number of patients showed negative KOH mount (71.5%), saline wet mount was negative in 80% of patients in antimicrobial agents + probiotics group. Conclusion: From the present interventional study, probiotics along with antimicrobial agents showed better improvement than antimicrobial agents alone. Hence, supplementation of probiotics along with antimicrobial agents provides better efficacy than antimicrobial agents alone in treating vulvovaginal infections.